A lifestyle intervention with an energy-restricted Mediterranean diet and physical activity enhances HDL function: a substudy of the PREDIMED-Plus randomized controlled trial. Issue 5 (28th September 2021) - Sanllorente, Albert; Soria-Florido, María Trinidad; Castañer, Olga; Lassale, Camille; Salas-Salvadó, Jordi; Martínez-González, Miguel Ángel; Subirana, Isaac; Ros, Emilio; Corella, Dolores; Estruch, Ramón; Tinahones, Francisco J; Hernáez, Álvaro; et al.
ABSTRACT: Background: Consumption of a Mediterranean diet, adequate levels of physical activity, and energy-restricted lifestyle interventions have been individually associated with improvements in HDL functions. Evidence of intensive interventions with calorie restriction and physical activity is, however, scarce. Objectives: To determine whether an intensive lifestyle intervention with an energy-restricted Mediterranean diet plus physical activity enhanced HDL function compared to a non-hypocaloric Mediterranean eating pattern without physical activity. Methods: In 391 older adults with metabolic syndrome (mean age, 65 years; mean BMI, 33.3 kg/m 2 ) from 1 of the Prevención con Dieta Mediterránea-Plus trial centers, we evaluated the impact of a 6-month intervention with an energy-restricted Mediterranean diet plus physical activity (intensive lifestyle; n  = 190) relative to a nonrestrictive Mediterranean diet without physical activity (control; n  = 201) on a set of HDL functional traits. These included cholesterol efflux capacity, HDL oxidative/inflammatory index, HDL oxidation, and levels of complement component 3, serum amyloid A, sphingosine-1-phosphate, triglycerides, and apolipoproteins A-I, A-IV, C-III, and E in apoB-depleted plasma. Results: The intensive-lifestyle intervention participants displayed greater 6-month weight reductions (−3.83 kg; 95% CI: −4.57 to −3.09 kg) but no changes in HDL cholesterol compared with control-diet participants. Regarding HDL functional traits, the intensive lifestyle decreased triglyceride levels (−0.15 mg/g protein; 95% CI: −0.29 to −0.014 mg/g protein) and apoC-III (−0.11 mg/g protein; 95% CI: −0.18 to −0.026 mg/g protein) compared to the control diet, with weight loss being the essential mediator (proportions of mediation were 77.4% and 72.1% for triglycerides and apoC-III levels in HDL, respectively). Conclusions: In older adults with metabolic syndrome, an energy-restricted Mediterranean diet plus physical activity improved the HDL triglyceride metabolism compared with a nonrestrictive Mediterranean diet without physical activity. This trial is registered at isrctn.com as ISRCTN89898870.